2018
DOI: 10.1093/jrr/rry107
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate dehydrogenase predicts survival in small-cell lung cancer patients with brain metastases that were treated with whole-brain radiotherapy

Abstract: This study aimed to identify factors that predict prognosis after radiotherapy for brain metastases (BMs) from small-cell lung cancer (SCLC). This study retrospectively evaluated 48 consecutive patients who underwent whole-brain radiotherapy (WBRT) for BMs from SCLC between February 2008 and December 2017. WBRT was delivered at a median dose of 30 Gy (range: 30–40 Gy) in 10 fractions (range: 10–16 fractions). Clinical factors were tested for associations with overall survival after WBRT. The median survival an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Our results point toward the importance of an adequate assessment of PS when evaluating treatment options for patients with ED, as a patients with poor PS may not derive meaningful benefit of PDCT [25]. In our analyses, a high LDH level was an independent prognostic factor in ED patients [21,27]. PCI was also associated with a better prognosis in ED patients as reported before [28].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Our results point toward the importance of an adequate assessment of PS when evaluating treatment options for patients with ED, as a patients with poor PS may not derive meaningful benefit of PDCT [25]. In our analyses, a high LDH level was an independent prognostic factor in ED patients [21,27]. PCI was also associated with a better prognosis in ED patients as reported before [28].…”
Section: Discussionmentioning
confidence: 49%
“…A log-transformed approach was instead chosen for CRP and LDH since the distribution of these lab values was skewed. These clinical and laboratory characteristics were chosen since they are routinely obtained at Karolinska University Hospital and previously have been shown to be prognostically relevant in SCLC patients [20,21].…”
Section: Co-variatesmentioning
confidence: 99%
“…Similar conclusions were reported by Anami et al, who found that elevated lactate dehydrogenase level might serve as a highly valuable marker for identifying patients with brain metastases from small cell lung cancer who could have poor survival outcomes. They also observed that higher LDH levels correlated strongly with shorter survival of patients with small-cell lung cancer (SCLC) [73].…”
Section: Lactate Dehydrogenase As a Predictive Markermentioning
confidence: 94%
“…Fortunately, many patients benefit from these treatments, both in terms of symptom control or prevention, radiological disease control, and overall survival. However, a subset of patients is at risk of early death just few weeks after diagnosis of brain metastases [6][7][8][9]. It is therefore of utmost importance to assess each patient's prognosis at the time of diagnosis of brain metastases, in order to provide guidance and to avoid an DOI: 10.1159/000506954 obvious mismatch between intensity of therapeutic measures and outcome.…”
Section: Introductionmentioning
confidence: 99%